Efforts to Improve Mathematics Learning Outcomes Through Problem-Based Learning for Grade IV Students of SDN Tanjung Jati 2 - Kholifatul Mukaromah; Melinda Ayu Puspitasari; Moh. Syarif Hidayat (Journal of Action Research in Education, 2025)
This research aims to improve mathematics learning outcomes in the Problem Based Learning (PBL) learning model. This research is classroom action research with the research subject being class IV of SDN TANJUNG JATI 2 for the 2024/2025 academic year and the research object is the students' mathematics learning outcomes. This research was carried out in two cycles where the application of the Problem Based Learning learning model was in cycle 2. Data was collected by observation, affective domain student learning outcomes questionnaires, field notes, written tests and documentation. Data were analyzed using triangulation techniques and qualitative descriptions. Based on the research results, it can be concluded that the Problem Based Learning (PBL) learning model can improve the learning outcomes of class IV students at SDN Tanjung Jati 2